Dried Grassmeal in the Diets of Weaner Rabbits: Effect On Growth And Carcass Characteristics - Uza, O.; Ayoade, J. A.; Shaahu, D.T.; Ahamefule, F.O.; Yusuf, T. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
Growth and carcass characteristics of weaner rabbits fed diets containing different levels of dried grass meal were evaluated in a 62-day trial. Twelve weaner rabbits of 4-6 weeks of age, averaging 908 g in weight were randomly divided into three groups of 4 animals each and replicated four times with a rabbit per replicate. These rabbits were assigned three different diets (1, 2 and 3) containing dried grass meal replacing rice offal at 0, 5.5 and 11% in a completely randomized design. Results showed that body weight (g) and ADFI did not differ (P>0.05) among the treatment groups. FCR followed a similar pattern. ADG was significant (P<0.05); diet 3 promoted the best gain (18.17 g), though similar to results obtained for rabbits fed diet 2 (15.08 g) which differed significantly (P<0.05) with daily body gain of animals on control diet (13.30 g). The slaughter weights, unsigned weight and dressed weight of rabbits fed diets 2 and 3 were highest and similar (P<0.05) while rabbit on control had the least values for these parameters. Headless singed weights were superior (P<0.05) for rabbits fed diet 3 (1.13 g) while rabbits on other treatment groups had the least and similar headless singed weights values. Dressing percentage was marginally enhanced for rabbits fed diet 3 but this was not significant (P>0.05). Therefore, dried grass meal can replace rice offal up to 11% in rabbit diet without adverse effect on growth and carcass characteristics of rabbits.